Bouvaist cubic of a triangle in an isotropic plane - Kolar-Šuper, Ružica (Array, 2019)
The cubic in an isotropic plane which passes through the intersections of the sides of an orthic triangle with the sides of a complementary triangle of a given triangle, and through the point which is complementary to the Steiner point of triangle is studied in this paper. It is proved that its non-isotropic asymptote is parallel to Lemoine line of a given triangle.